Controllably self-assembled graphene-supported Au@Pt bimetallic nanodendrites as superior electrocatalysts for methanol oxidation in direct methanol fuel cells. Issue 19 (25th April 2016) - Yuan, Weiyong; Fan, Xiuling; Cui, Zhi Ming; Chen, Tao; Dong, Zhili; Li, Chang Ming
Abstract : Graphene-supported Au@Pt bimetallic nanodendrites were synthesized by combining self-assembly with in situ seeded growth, showing remarkable electrocatalytic performance toward methanol oxidation. Abstract : Controllable growth of highly dense and uniform Pt nanostructures on graphene could greatly increase the electrocatalytic activity and Pt utilization for methanol oxidation in direct methanol fuel cells (DMFCs), but still presents a great challenge. This study reports a novel strategy of combining self-assembly with in situ seeded growth to fabricate graphene supported Pt nanostructures. Using self-assembled gold nanoparticles as the seeds, highly dense, uniform and well-dispersed Au@Pt bimetallic nanodendrites supported on graphene were fabricated for the first time. The density, size and shape of the bimetallic nanostructure can be easily controlled by the fabrication conditions such as the number of deposition cycles, precursor concentration and reductant concentration. The graphene supported Au@Pt bimetallic nanodendrites display greatly enhanced electrocatalytic activity and durability toward methanol oxidation compared to graphene supported Pt nanostructures and commercial Pt/C (E-TEK). Their catalytic activity is also among the highest reported for other state-of-the-art commercial Pt/C and PtRu/C as well as for non-covalently polyelectrolyte-functionalized carbon-supported Pt and PtRu catalysts. Our strategy can be extended to other substrates and metal components to fabricate various supported core/shell bimetallic nanostructures for applications such as catalysis, sensing and electronics.